Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 3
a, ĐKXĐ: x>0, x\(\ne\)4
M=( \(\dfrac{\sqrt{x}}{\sqrt{x}-2}+\dfrac{\sqrt{x}}{\sqrt{x}+2}\)). \(\dfrac{\sqrt{x}+2}{\sqrt{4x}}\)
M= \(\left(\dfrac{\sqrt{x}\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}+\dfrac{\sqrt{x}\left(\sqrt{x}-2\right)}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}\right)\). \(\dfrac{\sqrt{x}+2}{\sqrt{4x}}\)
M= \(\dfrac{x+2\sqrt{x}+x-2\sqrt{x}}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\). \(\dfrac{\sqrt{x}+2}{\sqrt{4x}}\)
M= \(\dfrac{2x}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}.\dfrac{\sqrt{x}+2}{\sqrt{4x}}\)
M= \(\dfrac{\sqrt{x}}{\sqrt{x}-2}\)
b, Thay x= \(6+4\sqrt{2}\) ( x>0, x\(\ne\)4) ta có:
M= \(\dfrac{\sqrt{6+4\sqrt{2}}}{\sqrt{6+4\sqrt{2}}-2}\)
= \(\dfrac{\sqrt{\left(\sqrt{2}+2\right)^2}}{\sqrt{\left(\sqrt{2}+2\right)^2-2}}\) = \(\dfrac{\sqrt{2}+2}{\sqrt{2}+2-2}\)
= \(\dfrac{\sqrt{2}\left(1+\sqrt{2}\right)}{\sqrt{2}}\) = \(1+\sqrt{2}\)
Vậy khi x= \(6+4\sqrt{2}\) thì M= \(1+\sqrt{2}\)
c, Để M<1 <=> \(\dfrac{\sqrt{x}}{\sqrt{x}-2}< 1\)
<=> \(\dfrac{\sqrt{x}}{\sqrt{x}-2}-\dfrac{\sqrt{x}-2}{\sqrt{x}-2}< 0\)
<=> \(\dfrac{2}{\sqrt{x}-2}< 0\)
Vì 2>0 <=> \(\sqrt{x}-2< 0\)
<=> \(\sqrt{x}< 2\)
<=> x<4
Vậy để M<1 thì 0<x<4
<=>
Câu 2
a, \(\sqrt{3x+2}=5\) (x\(\ge\dfrac{-2}{3}\))
<=> \(\sqrt{3x+2}=\sqrt{25}\)
<=> 3x+2=25
<=> 3x= 23
<=> x=\(\dfrac{23}{3}\)
Vậy S= \(\left\{\dfrac{23}{3}\right\}\)
\(T=\sqrt{x^2-x+2}+\sqrt{x^2+x+2}\)
\(T^2=x^2-x+2+x^2+x+2+2\sqrt{\left(x^2-x+2\right)\left(x^2+x+2\right)}\)
\(T^2=2x^2+4+2\sqrt{\left(x^2+2\right)^2-x^2}\)
\(T^2=2x^2+4+2\sqrt{x^4+4x^2+4-x^2}\)
\(T^2=2x^2+4+2\sqrt{x^4+3x^2+4}\)
Nhận xét : \(2x^2\ge0\forall x\)
\(x^4+3x^2+4=x^2\left(x^2+3\right)+4\)
Có : \(x^2\ge0,x^2+3\ge0\forall x\)nên
\(\Rightarrow x^2\left(x^2+3\right)\ge0\forall x\)
Cho nên \(x^4+3x^2+4\ge4\)
Vậy \(T^2=2x^2+4+2\sqrt{x^4+3x^2+4}\ge4+2\sqrt{4}=4+4=8\)
Do \(T^2\ge8\)nên :
\(\Rightarrow A\ge2\sqrt{2}\)
Dấu " = " xảy ra \(\Leftrightarrow x=0\)